2005
DOI: 10.1128/aac.49.11.4515-4520.2005
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities of Antiviral-Resistant Influenza Viruses to Novel Neuraminidase Inhibitors

Abstract: The susceptibilities of five zanamivir-resistant and six oseltamivir-resistant influenza viruses were assessed against four neuraminidase (NA) inhibitors, including peramivir and A-315675, by a fluorometric NA activity inhibition assay. The enzyme activity of a majority of the variants was effectively inhibited by either A-315675 or both peramivir and A-315675 (50% inhibitory concentration, <10 nM). A novel oseltamivir-resistant influenza virus B variant carrying substitution at residue 198 (Asp3Asn) (N2 numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
155
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(168 citation statements)
references
References 40 publications
8
155
1
4
Order By: Relevance
“…Only two substitutions, those at residues E119 and R292, were found in all three avian NA subtypes investigated and conferred some level of NAI resistance. The E119V NA mutation, found in both N7 and N9 subtypes in the present study, is a clinically relevant mutation in human N2 viruses of group 2 NAs by OS treatment and is associated with highly reduced inhibition by OS (18,19). The mutation also confers resistance to multiple NAIs in N1 subtype of group 1 NAs but significantly impairs their viral fitness (61,62).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Only two substitutions, those at residues E119 and R292, were found in all three avian NA subtypes investigated and conferred some level of NAI resistance. The E119V NA mutation, found in both N7 and N9 subtypes in the present study, is a clinically relevant mutation in human N2 viruses of group 2 NAs by OS treatment and is associated with highly reduced inhibition by OS (18,19). The mutation also confers resistance to multiple NAIs in N1 subtype of group 1 NAs but significantly impairs their viral fitness (61,62).…”
Section: Discussionmentioning
confidence: 87%
“…R152 is a catalytic residue that directly interacts with the sialic acid moiety, and the resistant mutation R152K has been found only in influenza B virus-infected patient after treatment with ZA (19,57). Unlike highly reduced susceptibility to multiple NAIs that is conferred by R152K in influenza B virus, the R152W mutation was selected by OS and reduced inhibition by only OS and ZA in N7 virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, 2,3 -disubstituted tetrahydrofuran -5 -carboxylic acid derivatives have been described as infl uenza neuraminidase inhibitors, albeit with reduced inhibitory potency as compared to the corresponding pyrrolidine analogues. 77 Peramivir (RWJ -270201) and A -315675 represent novel neuraminidase inhibitors that were shown to retain activity against various zanamivir -and oseltamivir -resistant infl uenza A and B viruses: 78 Specifi cally, a new oseltamivir -resistant infl uenza B variant carrying the D198N substitution at the viral neuraminidase was found to retain susceptibility to peramivir and A -315675. Also, the neuraminidase E119V mutant displaying 6000 -fold lower susceptibility to oseltamivir and 175 -fold lower susceptibility to zanamivir than did wild -type virus still retained full susceptibility to A -315675.…”
Section: Neuraminidase Inhibitors: Peramivir and Other Cyclopentane Omentioning
confidence: 99%
“…Oseltamivir-resistant H5N1 influenza viruses with mutations at positions H274Y and N294S of the NA have been isolated from patients during Le et al, 2005) and before (Saad et al, 2007) antiviral treatment. Thus far, such isolates remain sensitive to zanamivir McKimm-Breschkin, 2005;Mishin et al, 2005); however, new H5N1 isolates with mutations not previously reported to be associated with resistance show decreased sensitivity to oseltamivir and zanamivir in vitro (Hurt et al, 2007;McKimmBreschkin et al, 2007). New approaches for the control of infection with highly pathogenic influenza viruses must be explored; these may include novel antiviral drugs, combinations of antivirals, or optimization of the existing antiviral regimens (dosage, duration and route of administration).…”
Section: Introductionmentioning
confidence: 99%